Maßnahmen zur Vermeidung von Altersarmut: Makroökonomische Folgen und Verteilungseffekte - Lars P. Feld; Manuel Kallweit; Anabell Kohlmeier (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik, 2013)
There is an intensive debate about old-age poverty in Germany that has induced political parties to develop proposals for higher pensions of poor pensioners in light of the federal elections of September 2013. In addition, several proposals from economists aim at reforming the pension system in a way that mitigates oldage poverty. In this paper, we consider these proposals in a computable general equilibrium model in order to derive their effects on the income distribution, on employment, on the capital stock and on GDP. Our results indicate that negative employment, capital and GDP effects are induced by such reforms as compared to the alternative of basic means-tested social welfare in old-age. Moreover, the strongest beneficiaries would be the currently higher age employees with low income and much less the respective younger employees, while younger and higher age employees with high and medium incomes will lose.
Keywords: 330